Gay Romance ‘Heated Rivalry’ Is Reigniting a Troubling Debate - Schriefer, Natalie (Bloomberg.com, 2025)
Heated Rivalry, based on the second book in Rachel Reid’s “Game Changers” series, has been a hit for HBO Max. Critics have called the gay romance about hockey players one of the best queer TV shows, praising it as “sexy” and “significant.” Beyond these glowing reviews, though, there is another discourse. Heated Rivalry’s success has reignited an unhealthy debate over who gets to tell the stories of marginalized communities — a debate that has proven harmful to closeted creatives in the past and
Keywords: Art; Career; Environment; Equality; Jordan; NETFLIX INC; NEW YORK TIMES CO-A; Rachel Reid; TWITTER INC; Youtube; dept.hhs; view